Football and Its Politicisation in Darjeeling - Binu Sundas (International Journal of Critical Diversity Studies, 2023)
Football in India and Darjeeling, like in many parts of the world, was introduced during the colonial period. Darjeeling was “gifted” to the British by the king of Sikkim in 1835 to build a sanatorium. A military recruiting depot was also soon established. Along with the military came missionary schools. These two elements of the British social system facilitated the gradual growth of football in the region. Many tournaments were played and football soon became part of the social landscape. The Herlihy Cup which started in the year 1917, the same year, the Hillmen’s Association submitted a refined version of the 1907 memorandum, demanding a “separate administrative unit” comprising the present-day Darjeeling and Kalimpong districts along with the Dooars areas, was the only tournament of that period to be played till today. Until the 1980s, when violent agitation for the creation of Gorkhaland took place, football and the state enjoyed a cordial client-patron relationship. The agitation and the subsequent signing of a tripartite agreement between the Government of India, the Government of West Bengal, and the Gorkha National Liberation Front for the creation of the semi-autonomous Darjeeling Gorkha Hill Council in 1988 changed the political landscape of Darjeeling. Football began to be used as a tool for asserting identity, leading to the old structure's breakdown. The tripartite agreement did not completely suppress the aspirations for creating Gorkhaland. In 2017 another round of agitation started. The agitation failed due to the betrayal of two leaders and the indiscriminate use of repressive apparatus by the state. To proclaim normalcy, football tournaments were initiated when fear and unfreedom were the norm and hegemony of power, domination and repression were the reality. This article is based on the methods of auto-ethnography and reflexivity and will try to highlight and analyze the relationship between football and politics in Darjeeling after the 1980s.